Method for catalyzing free radical polymerization at room temperature

By introducing specific nanoparticles into the polymerization system, the thermal decomposition temperature of the thermal initiator is reduced, and it spontaneously decomposes at room temperature, solving the problems of large energy consumption and low safety caused by high-temperature polymerization, and achieving efficient and safe free radicals Polymerization to prepare high molecular weight and narrow distribution polymer materials.

CN119119334AInactive Publication Date: 2024-12-13DUKE KUNSHAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411216019.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2024-12-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, free radical polymerization caused by thermal initiators requires high temperatures, resulting in large energy consumption, low safety, and is not suitable for temperature-sensitive systems, making it difficult to control the structure of polymer products, limiting the production and application of polymer materials.

Method used

By introducing nanoparticles, including metal oxides, metal phosphoric acid compounds or silicon oxides, such as CuO, TiO2, VO2, monodispersed silica, etc., to the polymerization system, the thermal decomposition temperature of the thermal initiator is reduced and the thermal initiator is kept at room temperature. Spontaneous decomposition produces free radicals and realizes free radical polymerization.

Benefits of technology

It realizes safe and efficient radical polymerization at room temperature, prepares high molecular weight and narrow distribution polymer materials, reduces production costs, is suitable for large-scale industrial production, and avoids the safety and structural control problems caused by high-temperature polymerization. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119334A_ABST
    Figure CN119119334A_ABST
Patent Text Reader

Abstract

The invention relates to a method for catalyzing free radical polymerization at room temperature, which comprises the step of introducing nano particles into a polymerization system, and the nano particles comprise metal oxide, metal phosphate compound, metal oxychloride or silicon oxide. According to the catalytic method, the thermal decomposition temperature of a common thermal initiator can be reduced to the room temperature, and room-temperature free radical polymerization of an oil-soluble or water-soluble monomer in a body, solution and emulsion system is initiated, so that various vinyl homopolymerized or copolymerized macromolecular materials are safely and efficiently prepared. The catalytic method is low in cost and easy to operate, does not require inert gas protection or high-purity raw materials, and is suitable for large-scale industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of polymer technology, in particular to a method for catalytic free radical polymerization at room temperature. Background Art

[0002] As one of the most commonly used materials, synthetic polymers have a global production of more than 400 million tons in 2021 and are growing at an annual rate of 3.4%. Vinyl polymer materials, such as polystyrene and polymethyl methacrylate, are the largest branch of synthetic polymers, and their polymerization mainly relies on free radical polymerization.

[0003] Thermal initiators are widely used in free radical polymerization reactions because of their low cost and suitability for large-scale production. Thermal initiators, including azobisisobutyronitrile (AIBN), benzoyl peroxide (BPO) and potassium persulfate (KPS), need to be heated to high temperatures (60°C or higher) to initiate free radical polymerization. Such high-temperature polymerization reactions have the disadvantages of high energy consumption, low safety, unsuitability for temperature-sensitive systems, and poor control of polymer product structure. In order to overcome the above problems caused by high-temperature polymerization, the following technologies are currently used to reduce the polymerization temperature:

[0004] 1. Room temperature or low temperature initiators: They can spontaneously decompose at room temperature to produce free radicals, but due to their high reactivity, strict safety standards need to be implemented in transportation and storage, making them difficult to use in actual production.

[0005] 2. Photoinitiation: Decomposition of initiators or monomer molecules by high-energy photons (gamma irradiation, UV light) to generate free radicals. This method has high requirements for equipment, and the initiation of polymerization is limited by the penetration depth of photons. It is currently only applicable to the production of thin film products.

[0006] 3. Redox initiation: Generate free radicals through a redox system. This method either uses heavy metal compounds as catalysts or can only be used for aqueous / emulsion polymerization, has a limited scope of application and may pollute the environment.

[0007] 4. Interface initiation: At room temperature, thermal initiators such as AIBN can spontaneously decompose at the water-oil interface, thereby initiating free radical polymerization. This method promotes the decomposition of the initiator at room temperature through the water-oil interface, so it is only applicable to emulsion polymerization.

[0008] Free radical polymerization using thermal initiators needs to be carried out at higher temperatures. High-temperature polymerization not only wastes energy, but also causes a series of reaction safety (Trommsdorff effect) and application restrictions (colloid template stability decreases with high temperature, biomolecules are inactivated at high temperature, low molecular weight / wide distribution products, etc.). Therefore, there is an urgent need in the art for a method of efficiently initiating free radical polymerization at room temperature. Summary of the invention

[0009] Problem that the invention aims to solve

[0010] In view of the above problems existing in the prior art, the object of the present invention is to provide a method capable of initiating free radical polymerization at room temperature.

[0011] Solutions for solving problems

[0012] The invention provides a method for catalytic free radical polymerization at room temperature. The method comprises introducing nanoparticles into a polymerization system. The nanoparticles comprise metal oxides, metal phosphate compounds, metal chloride oxides or silicon oxides.

[0013] Preferably, the nanoparticles are selected from one or more of CuO, Cu2O, Fe3O4, MnO2, RuO2, TiO2, VO2, V2O5, ZrO2, ZrOCl3, ZrP, ZnO, monodisperse silica, and fumed silica;

[0014] More preferably, the nanoparticles are selected from one or more of CuO, Cu2O, TiO2, VO2, ZrP, monodisperse silica, and fumed silica.

[0015] Preferably, the polymerization system is a bulk polymerization system or a solution polymerization system.

[0016] More preferably, the polymerization system is an olefin-containing polymerization system.

[0017] Preferably, the method comprises the following steps:

[0018] (1) dissolving the thermal initiator in the polymer monomer;

[0019] (2) adding the nanoparticles and reacting at room temperature in the dark; or

[0020] (1) dissolving a thermal initiator in a solvent;

[0021] (2) Adding polymer monomers and the nanoparticles, and reacting at room temperature in the dark.

[0022] Preferably, the added amount of the nanoparticles is 1 to 5 wt %.

[0023] Preferably, the polymer monomer is a vinyl monomer;

[0024] More preferably, the polymer monomer is selected from one or more of ethyl acrylate, styrene, vinyl acetate, methyl acrylate, butyl acrylate, acrylonitrile, acrylamide, and methyl methacrylate;

[0025] Further preferably, the polymer monomer is selected from one or more of styrene, acrylonitrile, acrylamide and methyl methacrylate.

[0026] Preferably, the thermal initiator in step (1) includes one or more of an azo thermal initiator, a peroxide thermal initiator, and a persulfate thermal initiator;

[0027] Preferably, the azo thermal initiator is selected from one or more of AIBN, ABVN, AIBA, and AIBI, preferably AIBN;

[0028] Preferably, the peroxide thermal initiator is selected from one or more of TBHP, BPO, CH335, and EHP, preferably BPO;

[0029] Preferably, the persulfate thermal initiator is selected from APS and / or KPS, preferably KPS.

[0030] Preferably, the solvent in step (1) comprises an aqueous solvent, an oily solvent or an emulsion;

[0031] More preferably, the solvent is water.

[0032] Preferably, the room temperature in step (2) is 10 to 40° C.

[0033] More preferably, the room temperature in step (2) is 20-40°C.

[0034] The present invention also provides a polymer prepared according to the method, wherein the polymer is a high molecular weight, narrow distribution high molecular weight homopolymer and / or copolymer.

[0035] Effects of the Invention

[0036] The catalytic method of the present invention can reduce the thermal decomposition temperature of a common thermal initiator to room temperature, and initiate the free radical polymerization of oil-soluble or water-soluble monomers in bulk, solution, and emulsion systems at room temperature, thereby safely and efficiently preparing various vinyl homopolymer or copolymer polymer materials. The catalytic method of the present invention is low in cost, easy to operate, does not require inert gas protection or high-purity raw materials, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Schematic diagram of nanoparticle-catalyzed decomposition of thermal initiators at room temperature.

[0038] Figure 2 PMMA is prepared by room temperature catalysis of monodisperse silica.

[0039] Figure 3 The temperature variation for the polymerization of acrylonitrile at 20 and 40°C.

[0040] Figure 4 It is PMMA prepared by conventional polymerization at 60°C. DETAILED DESCRIPTION

[0041] In order to make the technical solutions and beneficial effects of the present invention more clearly understandable, the following is a detailed description by listing specific embodiments. The drawings are not necessarily drawn to scale, and local features may be enlarged or reduced to more clearly show the details of the local features; unless otherwise defined, the technical and scientific terms used herein have the same meanings as those in the technical field to which this application belongs.

[0042] As used herein, the term "free radical polymerization" refers to the formation of high molecular weight macromolecules by the attack of free radicals on carbon-carbon double bonds in vinyl monomers.

[0043] As used herein, the term "thermal initiator" refers to a molecule that generates free radicals by isolytic decomposition at high temperatures, such as AIBN, BPO, and the like.

[0044] As used herein, the term "molecular weight distribution index" refers to the ratio of weight average molecular weight to number average molecular weight, reflecting the polydispersity of polymers.

[0045] As used herein, the term "Trommsdorff effect", also known as "self-acceleration phenomenon" or "gel effect", refers to the fact that during the polymerization reaction, as the monomers are gradually converted into polymers, the viscosity of the system continues to increase and the reaction rate increases significantly. Since the polymerization reaction is an exothermic reaction, if the large amount of heat generated by the Trommsdorff effect in a short period of time cannot be discharged in time, it will lead to a series of serious safety accidents such as implosion.

[0046] Unless otherwise specified, the materials and equipment used in the present invention can be obtained by conventional methods in the art, or through commercial channels, including but not limited to: Cabot, Xianfeng Nano, etc. Experimental methods without specific conditions are usually carried out under conventional conditions or conditions recommended by the manufacturer.

[0047] The invention provides a method for catalytic free radical polymerization at room temperature. The method comprises introducing nanoparticles into a polymerization system. The nanoparticles comprise metal oxides, metal phosphate compounds, metal chloride oxides or silicon oxides.

[0048] In certain embodiments, the nanoparticles are selected from one or more of metal oxides, metal phosphate compounds, metal oxychlorides, or silicon oxides.

[0049] In certain embodiments, the nanoparticles are selected from one or more of CuO, Cu2O, Fe3O4, MnO2, RuO2, TiO2, VO2, V2O5, ZrO2, ZrOCl3, ZrP, ZnO, monodisperse silica, and fumed silica.

[0050] In certain embodiments, the nanoparticles are selected from one or more of CuO, Cu2O, TiO2, VO2, ZrP, monodisperse silica, and fumed silica.

[0051] In certain embodiments, the nanoparticles are CuO.

[0052] In certain embodiments, the nanoparticles are Cu2O.

[0053] In certain embodiments, the nanoparticles are TiO2.

[0054] In certain embodiments, the nanoparticles are VO2.

[0055] In certain embodiments, the nanoparticles are ZrP.

[0056] In certain embodiments, the nanoparticles are monodisperse silica.

[0057] In certain embodiments, the nanoparticles are fumed silica.

[0058] In certain embodiments, the polymerization system is a bulk polymerization system or a solution polymerization system.

[0059] In certain embodiments, the polymerization system is a bulk polymerization system.

[0060] In certain embodiments, the polymerization system is a solution polymerization system.

[0061] In certain embodiments, the polymerization system is an olefinic group-containing polymerization system.

[0062] In certain embodiments, the method comprises the steps of:

[0063] (1) dissolving the thermal initiator in the polymer monomer;

[0064] (2) adding the nanoparticles and reacting at room temperature in the dark.

[0065] In certain embodiments, the method comprises the steps of:

[0066] (1) dissolving a thermal initiator in a solvent;

[0067] (2) Adding polymer monomers and the nanoparticles, and reacting at room temperature in the dark.

[0068] In certain embodiments, the amount of the nanoparticles added is 1 to 5 wt %.

[0069] In certain embodiments, the amount of the nanoparticles added is 1 wt%, or 1.1 wt%, or 1.2 wt%, or 1.3 wt%, or 1.4 wt%, or 1.5 wt%, or 1.6 wt%, or 1.7 wt%, or 1.8 wt%, or 1.9 wt%, or 2 wt%, or 2.1 wt%, or 2.2 wt%, or 2.3 wt%, or 2.4 wt%, or 2.5 wt%, or 2.6 wt%, or 2.7 wt%, or 2.8 wt%, or 2.9wt%, or 3wt%, or 3.1wt%, or 3.2wt%, or 3.3wt%, or 3.4wt%, or 3.5wt%, or 3.6wt%, or 3.7wt%, or 3.8wt%, or 3.9wt%, or 4wt%, or 4.1wt%, or 4.2wt%, or 4.3wt%, or 4.4wt%, or 4.5wt%, or 4.6wt%, or 4.7wt%, or 4.8wt%, or 4.9wt%, or 5wt%.

[0070] In certain embodiments, the polymerizable monomer is a vinyl monomer.

[0071] In certain embodiments, the polymer monomer is selected from one or more of ethyl acrylate, styrene, vinyl acetate, methyl acrylate, butyl acrylate, acrylonitrile, acrylamide, and methyl methacrylate.

[0072] In certain embodiments, the polymer monomer is selected from one or more of styrene, acrylonitrile, acrylamide, and methyl methacrylate.

[0073] In certain embodiments, the polymer monomer is styrene.

[0074] In certain embodiments, the polymerizable monomer is acrylonitrile.

[0075] In certain embodiments, the polymer monomer is acrylamide.

[0076] In certain embodiments, the polymerizable monomer is methyl methacrylate.

[0077] In certain embodiments, the thermal initiator in step (1) includes one or more of an azo thermal initiator, a peroxide thermal initiator, and a persulfate thermal initiator.

[0078] In certain embodiments, the thermal initiator in step (1) is an azo thermal initiator.

[0079] In certain embodiments, the azo thermal initiator is selected from one or more of AIBN, ABVN, AIBA, and AIBI.

[0080] In certain embodiments, the azo thermal initiator is AIBN.

[0081] In certain embodiments, the thermal initiator in step (1) is a peroxide thermal initiator.

[0082] In certain embodiments, the peroxide thermal initiator is selected from one or more of TBHP, BPO, CH335, and EHP.

[0083] In certain embodiments, the peroxide-based thermal initiator is BPO.

[0084] In certain embodiments, the thermal initiator in step (1) is a persulfate thermal initiator.

[0085] In certain embodiments, the persulfate thermal initiator is selected from APS and / or KPS.

[0086] In certain embodiments, the persulfate thermal initiator is KPS.

[0087] In certain embodiments, the solvent in step (1) comprises an aqueous solvent, an oily solvent or an emulsion;

[0088] In certain embodiments, the solvent is water.

[0089] In certain embodiments, the solvent is deionized water.

[0090] In certain embodiments, the room temperature in step (2) is 10-40°C.

[0091] In certain embodiments, the room temperature in step (2) is 10°C, or 11°C, or 12°C, or 13°C, or 14°C, or 15°C, or 16°C, or 17°C, or 18°C, or 19°C, or 20°C, or 21°C, or 22°C, or 23°C, or 24°C, or 25°C, or 26°C, or 27°C, or 28°C, or 29°C, or 30°C, or 31°C, or 32°C, or 33°C, or 34°C, or 35°C, or 36°C, or 37°C, or 38°C, or 39°C, or 40°C.

[0092] In certain embodiments, the room temperature in step (2) is 20-40°C.

[0093] The present invention also provides a polymer prepared according to the method, wherein the polymer is a high molecular weight, narrow distribution high molecular weight homopolymer and / or copolymer.

[0094] Example 1: Preparation of Nanoparticles

[0095] Fumed silica was purchased from Cabot; TiO2, VO2, CuO, and Cu2O were purchased from Xianfeng Nano.

[0096] Monodisperse silica 1: 45 mL of deionized water, 1.65 mL of NH3 and 100 mL of isopropanol were mixed for 10 minutes, 24.5 mL of TEOS was added dropwise to the above solution under magnetic stirring at room temperature, and stirred continuously for 5 hours. The mixture was washed with water and ethanol four times, and then dried in an oven at 150°C for 5 hours to obtain monodisperse silica 1 with a particle size of 30 nm.

[0097] Monodisperse silica 2: 7.8 mL of TEOS and 7.8 mL of ethanol were mixed for 10 minutes to obtain solution A. 2.5 mL of NH3, 5 mL of water and 7.8 mL of ethanol were mixed for 10 minutes to obtain solution B. Solution A and solution B were mixed at 40°C and a fixed stirring speed (450 rpm) for 30 minutes, and then dried in an oven at 60°C for 3 hours to obtain monodisperse silica 2 with a particle size of 200 nm.

[0098] ZrP: A mixture of 175 mg NH4F and 1.5 g ZrOCl2·8H2O was ground in an agate mortar and then transferred to a 30 ml polypropylene bottle. 0.941 mL H3PO4 was added dropwise to the solid mixture. The viscous solid mixture was stirred with a glass rod to ensure homogeneity, the container was covered with a lid, and placed in an oven at 100 °C for 24 h. The solid product was washed by centrifugation with deionized water and then dried in an oven at 60 °C for 24 h to obtain ZrP nanorods.

[0099] Example 2: Thermal initiator decomposition efficiency

[0100] 40 mg of thermal initiator AIBN was dissolved in 2 ml of toluene, and then 40 mg of nanoparticles (transition metal-based nanoparticles) were added, and the nanoparticles were precipitated at the bottom of the solution. The solution was placed in a room temperature and lightless environment (excluding the possibility of light initiation), and the solution was taken out at regular intervals to measure the ultraviolet absorption (At) at 344-346 nm, and the decomposition rate constant kd of AIBN under given conditions was calculated. The formula is shown below, and the results are shown in Table 1.

[0101]

[0102] Table 1: AIBN decomposition rate constants (10 -7 s -1 )

[0103] temperature Blank Group Monodisperse silica 1 Monodisperse silica 2 Fumed Silica ZrP Nanorods <![CDATA[TiO2]]> 20℃ 0 8.9 7.8 5.6 17.5 9.2 40℃ 0 41.4 49.7 63.6 47.5 37.5

[0104] The results showed that in samples without nanoparticles, AIBN hardly decomposed at 20 or 40°C, and thus could not generate free radicals. In samples with a small amount of nanoparticles, AIBN decomposed. During the decomposition of the thermal initiator, the nanoparticles played a catalytic role in reducing the decomposition activation energy, allowing AIBN, which originally had to be decomposed at more than 60°C, to efficiently generate free radicals at less than 40°C.

[0105] Example 3: Bulk Polymerization Styrene Polymerization Rate

[0106] 40 mg of thermal initiator AIBN was dissolved in 2 ml of styrene, and then 40 mg of nanoparticles (transition metal-based nanoparticles) were added, and the nanoparticles were precipitated at the bottom of the solution. The solution was placed in a room temperature and lightless environment (excluding the possibility of light initiation), and samples were taken out at regular intervals to measure the content of polymer solid products, and the polymerization rate Rp of styrene under given conditions was calculated. The formula is shown below, and the results are shown in Table 2.

[0107]

[0108] Table 2: Styrene polymerization rate (mol L -1 h -1 )

[0109] temperature Blank Group Monodisperse silica 1 Monodisperse silica 2 Fumed Silica ZrP Nanorods <![CDATA[TiO2]]> 20℃ 0 0.25 0.27 0.31 0.22 0.2 40℃ 0 0.57 0.55 0.61 0.64 0.52

[0110] The results showed that in the samples without nanoparticles, styrene hardly polymerized at 20 or 40 °C, which was related to the inability of AIBN to generate free radicals at this temperature.

[0111] Example 4: Bulk Polymerization Styrene Conversion

[0112] Weigh the sample mass after the reaction is completed, then subtract the mass of the nanoparticles to obtain the mass of the synthesized polymer. Divide the polymer mass by the mass of the monomer added before the reaction to calculate the conversion rate. In the samples with a small amount of nanoparticles added, styrene undergoes polymerization, as shown in Table 3. At 20°C, the conversion rate of styrene monomer reaction can reach 80-90% within 3 days.

[0113] Table 3: Conversion rate of styrene at 20°C (3 days)

[0114] Blank Group Monodisperse silica 1 Monodisperse silica 2 Fumed Silica ZrP Nanorods <![CDATA[TiO2]]> ~0% 82% 81% 87% 80% 80%

[0115] Example 5: Polymerization Rates of Other Oil-Soluble Vinyl Monomers

[0116] Other oil-soluble vinyl monomers can also be polymerized at 20 or 40° C. by nanoparticle catalysis, such as methyl methacrylate, whose polymerization rate is similar to that of styrene. The experimental steps are the same as those in Example 3, and the results are shown in Table 4.

[0117] Table 4: Polymerization rate of methyl methacrylate (mol L -1 h -1 )

[0118]

[0119]

[0120] The results show that when other oil-soluble thermal initiators are used, such as BPO instead of AIBN, the polymerization rate in the monomer is close to that of the system using AIBN under the catalysis of nanoparticles. For example, when fumed silica nanoparticles are used, the polymerization rates of methyl methacrylate initiated by AIBN or BPO are 0.31 and 0.28 mol L, respectively. -1 h -1 (20℃).

[0121] Example 6: Trommsdorff effect

[0122] Since the initiation step of the sample catalyzed by nanoparticles is carried out at room temperature, the entire polymerization process is mild and controllable. During the reaction, a K-type high-sensitivity thermocouple is placed on the surface of the reaction bottle to measure the temperature change during the reaction. Figure 2 As shown in the figure, the temperature of the polymerization reaction at room temperature of 20°C remained stable, while the temperature of the reaction at 40°C rose significantly, with the temperature of the reaction bottle rising by 30°C in 8 minutes. For the sample polymerized at 60°C, the reaction was too intense and the bottle shook, resulting in the inability to accurately measure the temperature. However, a large number of bubbles appeared in the polymerization product (such as Figure 3 For room temperature polymerization catalyzed by nanoparticles, even if the amount of reactants was increased by 15 times, no obvious Trommsdorff effect was observed (as shown in Figure 2). Figure 4 As shown). It can be seen that nanoparticle-catalyzed room temperature polymerization can effectively avoid Trommsdorfffect, improve the safety of the reaction process and reduce the use of cooling equipment.

[0123] Example 7: Bulk Polymerization Acrylonitrile Conversion Rate

[0124] 40 mg of thermal initiator AIBN was dissolved in 2 ml of acrylonitrile, and then 40 mg of nanoparticles (transition metal-based nanoparticles) were added, and the nanoparticles were precipitated at the bottom of the solution. The solution was placed in a room temperature and light-free (excluding the possibility of light initiation) environment, and the time required for the polymerization reaction to reach 90% conversion was recorded. The results are shown in Table 5.

[0125] Table 5: Time required for bulk polymerization to reach 90% conversion

[0126] temperature Blank Group Fumed Silica 20℃ 70h 7h 40℃ 4 h 40min

[0127] Example 8: Solution Polymerization Conversion Rate

[0128] 40 mg of water-soluble thermal initiator KPS was dissolved in 2 ml of deionized water, and then 1.34 g of water-soluble vinyl monomer acrylamide and 40 mg of nanoparticles (transition metal-based nanoparticles) were added, and the nanoparticles were precipitated at the bottom of the solution. The solution was placed in a room temperature and light-free (excluding the possibility of light initiation) environment, and the time required for the polymerization reaction to reach 90% conversion was recorded. The results are shown in Table 6.

[0129] Table 6: Time required for solution polymerization to reach 90% conversion

[0130]

[0131]

[0132] Example 9: Molecular weight and molecular weight distribution of polymer products

[0133] The polymers prepared by traditional high temperature polymerization (above 60°C), such as polymethyl methacrylate used to prepare electronic touch screens, have a weight average molecular weight of about 100 kg / mol and a wide molecular weight distribution (conventional free radical polymerization) PDI ~ 2. Under the same laboratory conditions, the molecular weights and molecular weight distributions of the products of room temperature polymerization catalyzed by nanoparticles and conventional high temperature polymerization are shown in Table 7.

[0134] Table 7: Molecular weight and molecular weight distribution of room temperature polymerization and high temperature polymerization products

[0135]

[0136] Room temperature free radical polymerization catalyzed by nanoparticles can produce high molecular weight, narrow distribution high molecular homopolymers and copolymers. For example, PMMA, the weight average molecular weight can reach 4000kg / mol and the molecular weight distribution index PDI <1.3. High molecular weight products have better mechanical and thermal properties, and the narrow molecular weight distribution ensures the reliability of the material.

[0137] It should be understood that the above embodiments are exemplary and are not intended to include all possible implementations included in the claims. Various modifications and changes may be made on the basis of the above embodiments without departing from the scope of the present disclosure. Similarly, the various technical features of the above embodiments may be arbitrarily combined to form other embodiments of the present invention that may not be explicitly described. Therefore, the above embodiments only express several implementations of the present invention and do not limit the scope of protection of the patent of the present invention.

Claims

1. A method for catalytic free radical polymerization at room temperature, It is characterized in that The method comprises introducing nanoparticles into a polymerization system, wherein the nanoparticles comprise metal oxides, metal phosphate compounds, metal oxychlorides or silicon oxides.

2. The method according to claim 1, It is characterized in that The nanoparticles are selected from CuO, Cu 2 O, Fe 3 O 4 、MnO 2 、RuO 2 、TiO 2 , VO 2 、V 2 O 5 、ZrO 2 、ZrOCl 3 , one or more of ZrP, ZnO, monodisperse silica, and fumed silica; Preferably, the nanoparticles are selected from CuO, Cu 2 O、TiO 2 , VO 2 , ZrP, monodisperse silica, and fumed silica.

3. The method according to claim 2, It is characterized in that The polymerization system is a bulk polymerization system or a solution polymerization system, Preferably, the polymerization system is an olefin-containing polymerization system.

4. The method according to claim 3, It is characterized in that The method comprises the following steps: (1) dissolving the thermal initiator in the polymer monomer; (2) adding the nanoparticles and reacting at room temperature in the dark; or (1) dissolving a thermal initiator in a solvent; (2) Adding polymer monomers and the nanoparticles, and reacting at room temperature in the dark.

5. The method according to claim 4, It is characterized in that The added amount of the nanoparticles is 1-5 wt %.

6. The method according to claim 4, It is characterized in that The polymer monomer is a vinyl monomer; Preferably, the polymer monomer is selected from one or more of ethyl acrylate, styrene, vinyl acetate, methyl acrylate, butyl acrylate, acrylonitrile, acrylamide, and methyl methacrylate; More preferably, the polymer monomer is selected from one or more of styrene, acrylonitrile, acrylamide and methyl methacrylate.

7. The method according to claim 4, It is characterized in that The thermal initiator in step (1) includes one or more of an azo thermal initiator, a peroxide thermal initiator, and a persulfate thermal initiator; Preferably, the azo thermal initiator is selected from one or more of AIBN, ABVN, AIBA, and AIBI, preferably AIBN; Preferably, the peroxide thermal initiator is selected from one or more of TBHP, BPO, CH335, and EHP, preferably BPO; Preferably, the persulfate thermal initiator is selected from APS and / or KPS, preferably KPS.

8. The method according to claim 4, It is characterized in that The solvent in step (1) includes an aqueous solvent, an oily solvent or an emulsion; Preferably, the solvent is water.

9. The method according to claim 4, It is characterized in that The room temperature in step (2) is 10 to 40° C. Preferably, the room temperature in step (2) is 20-40°C.

10. A polymer prepared according to the method of claims 1 to 9, It is characterized in that The polymer is a high molecular weight, narrow distribution high molecular weight homopolymer and / or copolymer.